Pain research and children and adolescents with severe intellectual disability: ethical challenges and imperatives - Raskoff, SZ; Thurm, A; Miguel, HO; Kim, SYH; Quezado, ZMN (Elsevier, 2022)
Children with severe intellectual disabilities encounter inequities in pain-related care, yet little pain research involves this population. A considerable issue with pain research in this population is its ethical complexity. This Viewpoint delineates the ethical challenges of pain research involving children (aged 2–12 years) and adolescents (aged 13–21 years) with severe intellectual disabilities. There are two main issues. First, some of the standard methods for assessing pain and pain sensitivity are not suitable for individuals with severe intellectual disability, who are often non-verbal and unable to understand or follow instructions. Second, children and adolescents with severe intellectual disability cannot provide informed consent or assent to participate in pain research, and their dissent is not always recognised. The existing ethical guidelines for pain research by the International Association for the Study of Pain provide helpful, but general, guidance. This Viewpoint supplements these guidelines and uses a well established framework for assessing the ethics of clinical research to highlight points relevant to designing, doing, reviewing, and evaluating research involving children and adolescents with severe intellectual disability, focusing on issues that are unaddressed in existing guidance.